Using English Movie with Delay and Non Delay Subtitle to Improve Listening Skill - Muh. Ikhlasul Amal; Syahdan Syahdan; Risal Pandi; Halid M; Arialdi Arialdi (LETS: Journal of Linguistics and English Teaching Studies, 2022)
The aim of the study was to analyze and describe the process of improving students’ listeningskill for eleventh grade students of MAN 1 Majene, West Sulawesi Province through watchingEnglish movies. The subject of this research is XI Agama 2 Class that consisted of 16 students. Themethod used in this study is Classroom Action Research (CAR) which the writer workscollaboratively with the English teacher. The results in this study indicate that there wasimprovement of the students’ skill listening. Most of the students gradually gained good scores at theend of the cycle. The data were collected from a questionnaire, observation note of performance,pre-test and post-test. The study was conducted with cycle model through the steps of planning,conducting, observation, and reflection. The results of this study show a significant relationshipbetween students' learning by English movie with delay subtitle related to their listening skills as shown in their improvement of post-test and positive responses of students than English moviewith not delay. The questionnaire shows that more than 75% students felt easy to understandlistening materials from native speakers. Consequently, it was suggested that teaching learningprocess using English movie with English subtitle is recommended into learning process toimprove students' listening skills in English language classroom. In conclusion, watching Englishmovie can improve students listening skill.